Employee performance modelling using system dynamics - Alefari, Mudhafar Rashed Saeed All Warea (Cranfield University, 2019)
Employee performance is something dynamic, but can have great impact on the overall performance of any company. This is understood by companies and human resource management departments are responsible for measuring the performance of the employees, and come up with ideas on how to improve this constantly. Such practices include training of employees, providing initiatives such as bonuses and day offs. Furthermore, the literature review has highlighted that leadership style can have a great impact as well. Looking in the literature of employee performance, it was clear as well that there has not been a model that can be used for predicting the impact of such initiatives from systems point of view. So the initial aim was to develop such a model that can help manufacturing companies better handle the dynamic nature of employee performance and if possible help with the decision making when deciding which initiatives to be introduced. The literature review was focused in identifying the factors that have an impact on the employee performance and their possible interrelations. Then the best modelling approach was investigated. Modelling techniques such as discrete event simulation, agent based modelling and system dynamics were considered, with the latter selected at the end as the focus is on the impact of the change of policies and not the individual employees who cannot be modelled due to the random way of their behaviour. System dynamics models were developed based on this analysis and collecting data protocols were formulated for collecting information from companies. The models were validated in two companies in UAE. They can predict the impact that specific changes in policies will have in the employee performance and can guide the companies about what changes they should introduce
Keywords: Employee performance; Modelling; Manufacturing